Essential Factors and Strategies Focused on the Design of a Management Model to Reduce Gender-Based Violence Against Women - Roxana, Granda-Campoverde; Christian, Bermeo-Valencia; Gabriela, Bermeo-Valencia (Journal of Ecohumanism, 2024)
The study focused on identifying the essential factors and strategies needed to design an efficient management model aimed at reducing gender-based violence against women and promoting structural change within the community of San Francisco de Milagro, Ecuador. Using a qualitative and participatory approach, the methodology included emancipatory workshops with women and local female leaders, as well as in-depth interviews with specialists in the field. Among the most relevant findings are the importance of providing comprehensive and personalized support to victims, fostering economic inclusion, implementing community awareness campaigns, utilizing technological tools for efficient management, and basing decision-making on reliable data. These key factors and strategies not only address the immediate needs of affected women but also serve as catalysts for social transformation, with high potential for replicability in other similar contexts, both in Ecuador and across Latin America.